Foreign Remittances And Nigeria’s Economic Growth (1990 – 2018) - Egbulonu, Kelechukwu Godslove; Chukuezi, Oluchi Elleen (Advances in Social Sciences Research Journal, 2019)
Between 2010 and 2017, remittances inflows averaged a whopping 20 billon US Dollars per annum, more than double the foreign direct investment [FDI] figures for the period under review and more than 500 per cent of Nigeria commercial service exports. The figures could be comparatively intimidating when remittances inflows from unapproved and informal sources are taken into account. To this end it becomes imperative to consider the impact these remittances have had so far on the Nigerian economy both at the micro and macro levels. The ADF test was used to test for stationarity. The variables were all found to be integrated at 1st difference so we used the OLS technique to analyze our data. Results show a positive relationship between foreign remittances and economic growth. Also a strong two-way relationship was established between foreign remittances and foreign external reserve. Foreign remittances have come to be a major source of income for Nigerian families and households. Infant mortality rate which was included in our model as a measure of social welfare and human development was also seen to be on the decline and having no causality relationship with foreign remittances. This was rightly so because, as the study shows, the expenditure pattern of foreign receipts by households is tilted towards consumption. The study recommends the need for the country to strengthen the institutional framework required to harness the benefits of foreign remittances.